Studi Keandalan Penggunaan Cubicle 20 kV Double Incoming dengan Perencanaan Setting ATS untuk Optimalisasi Pembebanan Pelanggan di Atas 1 MVA pada PLN APJ Surakarta - Prabowo, Dharu Rendro Anom, Ir. Jatmiko, MT (2016)
Surakarta City is one of the center of trading, industry, and tourism which is still growing. In process of growing, it needs several proponents factor such as stabil and good electricity resource, where the longer the need will always increase. with the economycs growth about 6 %, Surakarta City needs electric growth for about 2 x 6 % = 12 %. With the increasing hospitality and entertainment district in the region Surakarta it is absolutely necessary a reliability in electricity requirement will be mainly on the customer side, for that rise, we need Cubicle Double Incoming. The planning to change the setting on each feeder are needed for reach out more better reliability, by applying the appropriate ATS setting on the feeder so the customer will happen only goes out in a very short time for one disorder. Load factor calculation is required for planning of each feeder so when there is fault, it will not give more affect if it's will change to second feeder. Load factor JJR 11 is 0.45 and JJR 08 is 0.36. The application of feeder normal and standby setting, we can get that makes optimalization of reliability in JJR 11 feeder to become more higher, that from average 2013-2015 SAIDI 3,5 hours/costumers/year and SAIFI 6,33 time/costumers/year to become SAIDI 0,0003 hour/costumers/year and SAIFI 0,0016 time/costumers/year. While for JJR 08 feeder is from SAIDI 4,48 hour/costumers/years and SAIFI 5,7 time/costumers/year become SAIDI 0,0014 hour/costumers/years and SAIFI 0,0022 time/costumers/year.